THE EFFECT OF CALCINATION TEMPERATURE OF TITANIUM DIOXIDE (TIO2) ON PHOTOCATALYTIC DEGRADATION OF CARBAMAZEPINE - Miranda Putri, Sharfina
Pharmaceutical pollutants are a grave concern due to its nature to be active in trace concentrations which effects are detrimental to the ecosystem and human health. Carbamazepine is the most prominent pharmaceutical pollutant among other pharmaceutical wastes in various parts of the world due to its low biodegradable properties. Photocatalytic degradation using semi-conductor-based catalysts is one of the promising methods that is suitable for carbamazepine degradation. TiO2 is a metal oxide semiconductor that has been broadly studied and used as a photocatalyst due to their abundance and highly photocatalytic activity. However, TiO2 has several disadvantages, including high electron-holes recombination rate, easily high agglomeration tendencies, and relatively high band gap energy (3,0-3,2 eV) which only activates under ultraviolet (UV) light. Thus, the TiO2 catalyst needs to be treated. Calcination is a common treatment that can be used to enhance photocatalytic activity of a catalyst. Calcination serves as one of the simplest yet effective method to alter the properties of TiO2 which contributes to its performance. The effect of calcination on the physicochemical properties of TiO2 were examined by XRD, SEM, BET, UV-Vis DRS, and Raman Spectroscopy. The results show that calcination temperature impacted more significantly towards its crystallinity and band gap than to other properties. The degradation of carbamazepine was done for 120 minutes and assessed using UV-Vis spectrophotometry. Among the temperature variations executed, TiO2-300 °C performed the best with 34.6% carbamazepine degraded. Its performance is supported by having the largest crystallite size and highest Raman intensity that increased its photocatalytic activity. The photocatalysis degradation products were also determined through LC-MS analysis. Out of the obtained results, BQM, BQD, and BaQM are common identified carbamazepine degradation products that have also been reported in published literatures.